Measuring Indigenous Product Attractivens trough Autenticity Perspective - Setyawati, Harini Abrilia; Trifiyanto, Kabul; Zakiyah, Tuti (AIBPM Publisher, 2023)
Batik is Indonesia's cultural heritage. Batik can be associated as an Indonesian brand. This research is aimed at examining the influence of the authenticity dimension which contains heritage, sincerity and quality commitment on indigenous product attractiveness. The research design used was expanatory. The number of samples in this study was 100 batik practitioners spread across 6 big cities in Central Java. The data collection method uses a questionnaire. Processing using SEM techniques and using the Smart PLS tool. The findings of this research are that heritage and quality commitment influence indigenous product attractiveness. Sincerity is proven to have no effect on indigenous product attractiveness. These findings contribute to research on how to build indigenous product attractiveness by strengthening authenticity values.